Electronic Word Of Mouth Brand Lokal Clothing Dengan Hashtag #Jakcloth Pada Media Sosial Instagram - Shafira Nafsa; Wahyuni, Itca Istia (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
Electronic word of mouth communication activities mark a shift from traditional communication to fast and global digital communication. This makes an opportunity or electronic word of mouth communication opportunity that can be used by companies as a step to promote a local clothing brand event. Jakarta Clothing is one of the companies that always maintains its existence by conducting regular campaigns through #JakCloth. The information provided by Jakarta Clothing can be conveyed and accepted by the wider community thanks to posts about #JakCloth made on the social media platform Instagram. This study aims to obtain findings and describe the electronic word of mouth of local clothing brands by #JakCloth on Instagram social media. The research method used is descriptive qualitative with a constructivism paradigm and data collection using interview techniques. he results of this study show that the quality of electronic word of mouth has gone viral but there is no specific concept and form designed for messaging activities #JakCloth. The quantity of electronic word of mouth #JakCloth has scheduling every day so that it can find out the interactions caused by followers, but there is no media monitoring scheme to find out the number of negative comments and photo tags. The credibility of the electronic word of mouth already has expertise in conveying #JakCloth messages, and has the trust of its followers.